ORGANIZATION OF THE PROCESS OF INDEPENDENT WORK OF STUDENTS IN THE CREDIT-MODULAR SYSTEM OF EDUCATION - Akbarova Sayyora Shukhratovna (European Journal of Humanities and Educational Advancements, 2023)
The article describes the importance and possibilities of independent work.In the development of students’ creativity in the credit-modular system of education. And also proposes a project (scheme) for organizing the process of independent work to develop the professional and creative competencies of students.